Clinical observational studies of potential participants’ current negative affect status for a clinical study of stem cell therapy for ischemic stroke: study protocol - Qin, Xixian; Li, Mengyao; Sun, Xuna; Dong, Peipei; Ji, Xiaofei; Li, Xiaoyan; Liu, Jing (Frontiers in Neurology, 2025)
IntroductionThe number of clinical research projects on stem cell therapy for stroke has increased annually with the rapid development of stem cells and regenerative medicine technologies. Some evidence indicates that negative emotions can affect the recruitment, compliance, retention, satisfaction, and even treatment outcomes of participants in clinical research. However, knowledge is insufficient regarding patients’ negative emotions associated with their participation in potential stem cell clinical research studies. Therefore, the study aims to investigate the negative emotions and main influencing factors for potential participants in clinical research on stem cell therapy for stroke.MethodsThis study protocol follows the Strengthening the Reporting of Observational Studies in Epidemiology Good Practice for Reporting Observational Studies. The questionnaire for this study will include 59 questions for potential participants regarding (1) their demographic characteristics, and (2) their levels of anxiety, depression, social support, general self-efficacy, and self-perceived burden.DiscussionThis study’s main strength is that it will contribute evidence on key predictors of negative affectivity in potential participants undergoing clinical trials of stem cell therapy for stroke. The results will support stem cell clinical center researchers in intervening in potential participants’ negative emotions, which is important for clinical research managers and policymakers worldwide.ConclusionThe study protocol developed in this study was validated through a rigorous development process, demonstrating scientific validity for negative affect evaluation in stem cell clinical research. This instrument provides clinicians with a standardized assessment protocol to monitor treatment-emergent emotional distress during experimental interventions, showing particular promise in identifying early psychological risks associated with novel biological therapies.